전도식 원자현미경을 이용한 ZnO 나노로드 기반 압전 나노발전기의 사이즈 의존성 평가 - 양이준; Yijun Yang; 김관래; Kwanlae Kim (대한금속·재료학회지, 58(1), 2020)
ZnO nanorods are one of the most studied materials because it can be facilely grown on a wide range of substrates at low temperature. ZnO exhibits piezoelectricity as well as semiconducting properties, and hence is applicable to piezoelectric nanogenerators and sensors. In the present work, the effect of ZnO nanorods’ size on piezoelectric performance was systematically studied using conductive atomic force microscopy (C-AFM). We measured the total C-AFM signal for an observing area and evaluated the piezoelectric performance of the ZnO nanorods based on this total C-AFM signal. First, five samples of ZnO nanorod with distinct aspect ratios were hydrothermally grown on silicon substrates. Afterwards, two types of AFM tips with different spring constants were used to conduct C-AFM as a function of aspect ratio. When the AFM tip with a 42 N/m spring constant was used for the C-AFM measurement, the total C-AFM signal continuously increased with increasing aspect ratio. The total C-AFM signal increased with increasing normal force, but fluctuated with increasing scan rate. The results of the C-AFM experimental measurements were compared with the open-circuit voltage and short-circuit current of ZnO-nanorod based piezoelectric nanogenerator. We show that using C-AFM is a facile and effective method for investigating the optimized aspect ratio of ZnO nanorods for piezoelectric power generation. (Received November 20, 2019; Accepted December 11, 2019)